Microstructural Control of Charge Transport in Organic Blend Thin‐Film Transistors. (17th July 2014) - Hunter, Simon; Chen, Jihua; Anthopoulos, Thomas D.
<x xml:space="preserve">Abstract</x> The charge‐transport processes in organic p‐channel transistors based on the small‐molecule 2, 8‐difluoro‐5, 11‐bis(triethylsilylethynyl)anthradithiophene (diF‐TES ADT), the polymer poly(triarylamine)(PTAA) and blends thereof are investigated. In the case of blend films, lateral conductive atomic force microscopy in combination with energy filtered transmission electron microscopy are used to study the evolution of charge transport as a function of blends composition, allowing direct correlation of the film's elemental composition and morphology with hole transport. Low‐temperature transport measurements reveal that optimized blend devices exhibit lower temperature dependence of hole mobility than pristine PTAA devices while also providing a narrower bandgap trap distribution than pristine diF‐TES ADT devices. These combined effects increase the mean hole mobility in optimized blends to 2.4 cm2/Vs – double the value measured for best diF‐TES ADT‐only devices. The bandgap trap distribution in transistors based on different diF‐TES ADT:PTAA blend ratios are compared and the act of blending these semiconductors is seen to reduce the trap distribution width yet increase the average trap energy compared to pristine diF‐TES ADT‐based devices. Our measurements suggest that an average trap energy of <75 meV and a trap distribution of <100 meV is needed to achieve optimum hole mobility in transistors based on diF‐TES ADT:PTAA blends.